Applying Harmony Degree Equation and TOPSIS Combined with Entropy Weights in Surface Water Classification - Kieu Diem Le; Giao Thanh Nguyen (Salehan Institute of Higher Education, 2024)
This study classified surface water quality in Can Tho city using the Eutrophication index, Harmony Degree Equation (HDE), and Technique of Order Preference by Similarity to Ideal Solution (TOPSIS). Water quality data were collected in two seasons at 38 locations with 18 parameters, including temperature, pH, dissolved oxygen (DO), biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), nitrite (N-NO2-), nitrate (N-NO3-), ammonium (N-NH4+), orthophosphate (P-PO43-), Fe, F-, Pb, As, Hg, coliform, chlorine-, and phosphorus-based pesticides. Water quality parameters are compared with national technical regulations on surface water quality (QCVN 08-MT:2015/BTNMT). The HDE method based on entropy weight has been applied to evaluate the comprehensive harmony degree of water quality for various purposes. In addition, the TOPSIS was also used to rank water quality at each location and determine the priority level that required mitigation and treatment solutions. Surface water quality in the study area had low dissolved oxygen content and was contaminated with TSS and coliform in both seasons. Water quality in the rainy season tends to decrease compared to the dry season. Based on HDE results, water quality in the study area in the dry season was assessed as suitable for domestic activities (needs treatment), irrigation, and navigation (HDII = 0.922), while the rainy season was suitable for irrigation and navigation (HDIII= 1.00). Moreover, surface water in the study area was in a state of potential eutrophication (EI > 0), in which eutrophication was higher during the dry season. The SW25 and SW28 were the most seriously eutrophic in the dry and rainy seasons, respectively. TOPSIS analysis indicated that SW22 and SW28 need treatment measures in both seasons; furthermore, SW2-SW4 (dry season) and SW23 (rainy season) also need appropriate management and impact mitigation solutions. SW4 was affected by the most significant seasonal impacts, which have high priority in the dry season and are lowest in the rainy season. Therefore, future studies are needed to identify specific sources of variation at these locations to reduce impacts. The study results provide helpful information for the decision-making process and water quality management. Doi: 10.28991/CEJ-2024-010-04-012 Full Text: PDF